New approaches to textual and image analysis in early Jewish and Christian studies - Schulthess, Sara; Allen, Garrick V.; Dilley, Paul C.; Phillips, Peter M. (Digital biblical studies, 2023)
"The digital world pervades the everyday lives of most people, and online tools have become an essential part of academic research in many disciplines. This reality is true also for biblical studies and related disciplines, areas that work with complex literary traditions, multiple manuscript cultures, and many methodological approaches to the problems at the centre of our discussions. This book shines a light on multiple new and emerging approaches to big disciplinary questions in biblical studies and beyond by highlight projects that are using digital tools, crafting computer-assisted approaches, and re-thinking the resources fundamental to the history of research"--